Estilos de aprendizaje y logros de aprendizaje en el área de comunicación en estudiantes del CRFA Santa Teresa I Zona, Yavarí 2023 - Falcon Sanchez, Cleysi (2025)
The study aimed to examine the relationship between learning styles and the achievements attained in the area of communication by secondary school students from CRFA Santa Teresa I Zona, in the district of Yavarí, during the 2023 school year. A quantitative, relational approach was employed, involving the participation of 142 students. Each of them answered two questionnaires: one to identify their learning styles and another to assess their achievements in communication. The findings revealed that students with more developed learning styles tended to achieve better results. The Spearman correlation test showed a very high positive relationship between the two variables (rho = 0.849; p < 0.001). This confirmed that when teaching was adapted to the students’ learning styles, their performance in the area of communication was significantly enhanced.